Evaluasi Karakter Morfologi Untuk Perbaikan Genetik Tanaman Pinang ( Areca Cathecu L.) di Padang Pariaman [Evaluation Of Morphological Characters For Arecanut (Areca Cathecu L.) Genetic Improvment In Padang Pariaman] - nFN Miftahorrachman; Firman Mantau; Dina Hervina (Buletin Palma, 2018)
Evaluation of morphological characters that directly affect the yield is the first step in genetic improvement of areca nut requiring knowledge of the relationship of morphological characters especially production. Morphological characters that are affected directly to yield will be utilized as a basis for selection to increase crop production. The aim of this research is to know morphological characters that directly influence the number of fruits per bunchas the basis of selection for plant improvement. The research was conducted in Korong Koto Padang and Korong Toboh, Nagari Sikucua, V Koto Kampung Dalam District, Padang Pariaman District, West Sumatera Province in December 2017. The result of path analysis indicated that character of girth (r = 0,4190), number of bunches (r = 0,4488), equatorial length of fruit (r = 0,8420), kernel weight (r = 0,5451), equatorial length of kernel (r = 0,6785), and polar length of kernel (r = 0,8443) has a direct effect on fruit production of Local arecanut. For Wangi arecanut only obtained one character that is equatorial length of fruit (r = 0.4984) that directly affect fruit production. The variety of appearance of Local areca nut characters leads to greater selection opportunities compared to Wangi arecanut.The research showed that for Local areca nut, the character of girth, number of bunches, equatorial length of whole fruit, kernel weight, equatorial length of kernel, and polar length of kernel can be used as the selection for the production, while for Wangi arecanut only characters of equatorial length of fruit can be used as the basis of selection.ABSTRAKPerbaikan genetik Pinang membutuhkan pengetahuan tentang hubungan karakter morfologi terutama dengan produksi. Penelitian bertujuan untuk mencari karakter-karakter morfologi yang berpengaruh secara langsung terhadap jumlah buah per tandan untuk dijadikan dasar seleksi bagi perbaikan tanaman. Penelitian dilakukan di Korong Koto Padang dan Korong Toboh, Nagari Sikucua, Kecamatan V Koto Kampung Dalam, Kabupaten Padang Pariaman, Provinsi Sumatera Barat  pada bulan Desember Tahun 2017. Analisa sidik lintas antara sebelas  karakter morfologi dan komponen buah dengan jumlah buah menggunakan rumus dari Singh dan Chaudary. Hasil analisis sidik lintas diperoleh karakter Lingkar Batang (r = 0.4190) , Jumlah Tandan (r = 0.4488) , Panjang Equatorial Buah Utuh (r = 0.8420), Berat Kernel (r = 0.5451) ,  Panjang Equatorial Kernel (r = 0.6785), dan Panjang Polar Kernel (r = 0.8443) berpengaruh langsung terhadap produksi buah untuk pinang local. Pada Pinang Wangi hanya diperoleh satu karakter yaitu Panjang Equatorial Buah (r = 0.4984) yang berpengaruh langsung terhadap produksi buah. Manfaat hasil penelitian ini adalah karakter-karakter Lingkar Batang, Jumlah Tandan, Panjang Equatorial Buah Utuh, Berat kernel, Panjang Equatorial Kernel, dan Panjang Polar Kernel dapat dijadikan dasar seleksi untuk perbaikan produksi Pinang Lokal, sementara untuk Pinang Wangi hanya karakter Panjang Equatorial Buah Utuh yang dapat dijadikan dasar seleksi.